AKSESIBILITAS DAN POLA KONSUMSI PANGAN PESERTA DAN BUKAN PESERTA KEGIATAN PEKARANGAN PANGAN LESTARI (P2L) DI PEKON BAHWAY KABUPATEN LAMPUNG BARAT - Rindika Haliza Oktarina; Wuryaningsih Dwi Sayekti; Dyah Aring Hepiana Lestari (Lampung University, 2023)
This research aims to analyze the level of vegetables accessibility of P2L participants and nonparticipants household, and identify the level of knowledge and consumption patterns of household participants and non-participants of the Pekarangan Pangan Lestari (P2L) activities. This research was conducted at Pelita Jaya Village using a survey method with a sample of 60 households consisting of 30 households participating in P2L activities, and 30 households nonparticipating in P2L activities. Data collection was carried out from May to August 2021. The data analysis method used was descriptive and verificative statistics. This method was used to measure the level of accessibility, the level of knowledge and food consumption patterns (scores of the Desirable Dietary Pattern (PPH)) of participating and nonparticipating households in P2L activities. The results showed that the level of accessibility of participant households was moderate, and that of nonparticipant households was difficult. The overall level of knowledge of P2L participated households regarding food diversification was better than that of nonparticipating households. The average PPH score for P2L participating households was 78.80 and that of nonparticipant households was 77.30. Key words: food accessibility, food consumption pattern, P2L, PPH